Imaging autobiographical memory - Fossati, Philippe (Les Laboratoires Servier, 2013)
Autobiographical memory (AM) defines the memory systems that encode, consolidate, and retrieve personal events and facts, AM is strongly related to self-perception and self representation. We review here the neural correlates of AM retrieval. AM retrieval encompasses a large neural network including the prefrontal, temporal, and parietal cortex, and limbic structures. All these regions subserve the cognitive processes (episodic remembering, cognitive control, self-processing, and scene construction) at play during memory retrieval. We emphasize the specific role of medial prefrontal cortex and precuneus in self-processing during autobiographical memory retrieval. Overall, these data call for further studies in psychiatric patients, to investigate the neural underpinnings of autobiographical memory and self-representation in mental disorders.